‘Talk Deep to Write deeper’: an exploration of the value of ‘deep talk’ in developing Cognitive Academic Language Proficiency (CALP) - Layton, Delia (South African Journal of Higher Education, 2016)
This paper presents the findings of a research project conducted with a group of first year university students for whom English was an additional language. The study showed that the process of group discussion enabled students to engage with each other’s ideas to develop their own arguments. In doing so, they began to ‘mimic’ academic discourse, moving from what Cummins (1996) termed ‘basic interpersonal communication skills’ (BICS) in the direction of ‘cognitive academic language proficiency’ (CALP). The research also found that background texts given prior to discussion helped inform and deepen the talk, allowing students to develop strong positions and to acknowledge opposing viewpoints thus strengthening their written arguments. The paper suggests that the development of written academic language in first year students in South Africa, whose background strongly emphasizes an oral tradition, can be enhanced by engaging in interactive group discussion. Keywords: Academic literacy, academic discourse, talk, language and identity.